The pattern and magnitude of "in vivo thrombin generation" differ in women with preeclampsia and in those with SGA fetuses without preeclampsia. (3rd July 2018) - Erez, Offer; Romero, Roberto; Vaisbuch, Edi; Kusanovic, Juan Pedro; Mazaki-Tovi, Shali; Chaiworapongsa, Tinnakorn; Gotsch, Francesca; Mittal, Pooja; Edwin, Samuel S.; Nhan-Chang, Chia-Ling; Than, Nandor Gabor; Kim, Chong Jai; et al.
Abstract: Objective: We aimed to determine the differences in the pattern and magnitude of thrombin generation between patients with preeclampsia (PE) and those with a small-for-gestational-age (SGA) fetus. Methods: This cross-sectional study included women in the following groups: (1) normal pregnancy (NP) ( n  = 49); (2) PE ( n  = 56); and (3) SGA ( n  = 28). Maternal plasma thrombin generation (TGA) was measured, calculating: (a) lag time (LT); (b) velocity index (VI); (c) peak thrombin concentration (PTC); (d) time-to-peak thrombin concentration (TPTC); and (e) endogenous thrombin potential (ETP). Results: (1) The median TPTC, VI, and ETP differed among the groups ( p  = .001, p  = .006, p  < .0001); 2) the median ETP was higher in the PE than in the NP ( p  < .0001) and SGA ( p  = .02) groups; 3) patients with SGA had a shorter median TPTC and a higher median VI than the NP ( p  = .002, p  = .012) and PE ( p  < .0001, p  = .006) groups. Conclusions: (1) Patients with PE had higher in vivo thrombin generation than women with NP and those with an SGA fetus; (2) the difference in TGA patterns between PE and SGA suggests that the latter group had faster TGA, while patients with PE had a longer reaction, generating more thrombin. This observation is important for the identification of a subset of patients who might benefit from low molecular-weight heparin.